On some aspects of furosemide routine prescription at acute respiratory distress syndrome at the prehospital stage - A. V. Dats (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
We studied the effect of furosemide application at the pre-hospital stage on survival rate and mortality risk in patients with acute respiratory distress syndrome. It was found that out of 665 patients admitted to intensive care units, 90 have been diagnosed with acute respiratory distress syndrome, of which 75 have noted decreased preload. Those patients were divided into two groups: group 1 (n = 28) received furosemide on the first day, group 2 (n = 47) did not receive furosemide. The patients of both groups matched by age, the severity of the condition and the severity of organ dysfunction. The 10-day survival rate in the patients with acute respiratory distress syndrome and reduced preload received furosemide at the pre-hospital stage made 11 % and was significantly lower than in the patients without furosemide - 43 % (p = 0.031). The frequency of multiple organ dysfunction syndrome in group 1 the was statistically higher than in patients without furosemide (93 % and 75 % respectively; p = 0.048). Furosemide administration in patients with acute respiratory distress syndrome and reduced preload 1.8 times increases the relative mortality risk (p = 0.032).